Thermal analysis of the steam boiler for the sterilization plant at Pepper Marketing Board (PMB) Kuching - Junaidi, E. (University Malaysia Sarawak, UNIMAS., 1999)
Sterilization Plant at Pepper Marketing Board (PMB) is capable of treating pepper to meet the stringent microbiological requirements of consuming countries. The Steam Boiler will supply the steam to two points of the Sterilization Plant.